THE PROBLEMS FACED BY MIDDLE EASTERN STUDENTS IN SPEAKING SKILLS - Prisila, Jihan Ayu; Ilzamudin Makmur; Yayu Heryatun (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2024)
This research aimed to discover the problems and their causes of Middle Eastern students in speaking skills. This research was conducted in Cairo, Egypt, specifically at Al-Azhar University. This research employed a descriptive analysis method with a qualitative approach. The participants included fifteen Middle Eastern students majoring in English. Interviews and questionnaires were employed for data collection of the research. The findings reveal that the most common problem faced by Middle Eastern students in terms of speaking skills is having a limited vocabulary (80%), as it has been proven that forming sentences in English is challenging for them. Additionally, other problems are followed by pronunciation (67%) as writing and pronunciation in English often differ significantly. Next, grammar deficiency (60%) due to a lack of the students’ ability to form coherent sentences, and deficiency in fluency when speaking (87%) due to difficulty imitating pauses, rhythm, stress, and intonation. Meanwhile, the causes of problems Middle Eastern students faced are a lack of self-confidence, fear of making mistakes, anxiety, embarrassment, and lack of support from both their universities and their external environments, such as family and community.